Progress on Exploring the Luminescent Properties of Organic Molecular Aggregates by Multiscale Modeling - Zhao, Jingyi; Zheng, Xiaoyan (Frontiers in Chemistry, 2022)
Luminescent molecular aggregates have attracted worldwide attentions because of their potential applications in many fields. The luminescent properties of organic aggregates are complicated and highly morphology-dependent, unraveling the intrinsic mechanism behind is urgent. This review summarizes recent works on investigating the structure-property relationships of organic molecular aggregates at different environments, including crystal, cocrystal, amorphous aggregate, and doped systems by multiscale modeling protocol. We aim to explore the influence of intermolecular non-covalent interactions on molecular packing and their photophysical properties and then pave the effective way to design, synthesize, and develop advanced organic luminescent materials.